A compressive assessment of patient satisfaction with ophthalmology with ophthalmology clinic services: A study at a tertiary care academic institution amidst and after the COVID-19 pandemic - Ronak Asodariya; Kavita R Bhatnagar; Manjari Tandon; Kirti Jaisingh; Jyoti Shakrawal; Seema Meena; Latika Pandey (Indian Journal of Ophthalmology)
Purpose: The study aims to systematically assess patient satisfaction concerning eye care services provided during and after the coronavirus disease 2019 (COVID-19) pandemic at a tertiary care academic institution. This work seeks to analyze the various dimensions influencing the holistic measure of overall patient contentment. Methods: A cohort of 2485 patients seeking physical consultation for ocular conditions at a tertiary care academic institution between April 2020 and December 2022 were recruited in a cross-sectional study. They were divided into two groups, viz. during the COVID period and post-COVID period. The primary focus was on evaluating overall satisfaction, measured through a validated patient satisfaction questionnaire (PSQ-18). Results: The study encompassed a total of 2485 participants, with 1242 individuals in the cohort during the COVID period and 1243 in the post-COVID phase. Within the COVID period subgroup, the mean age of male and female patients was 39.46 ± 19.31 and 39.58 ± 19.07 years, respectively. In the post-COVID subgroup, the mean age of male and female patients was 45.26 ± 19.38 and 45.36 ± 19.22 years, respectively. Examining the COVID subgroup, the highest satisfaction scores were observed in the domain of time spent with the doctor (3.3453 ± 0.59), followed by financial aspects (3.0816 ± 0.47), interpersonal manner (3.0589 ± 0.37), and accessibility and convenience (3.0585 ± 0.37). Notably, technical quality received the lowest satisfaction score (2.4763 ± 0.42). A statistically significant difference (P < 0.0001) was noted in the PSQ-18 scores between the two groups. In the post-COVID subgroup, patients expressed higher satisfaction with the technical quality of treatment, irrespective of the mode of management. However, financial satisfaction was better in the COVID group. Conclusion: Our study using the PSQ-18 questionnaire highlights significant variations in patient satisfaction with ophthalmology clinic services during and after the COVID era. Notably, time spent with the doctor scored the highest, emphasizing its positive impact. However, addressing concerns related to technical quality is crucial for overall improvement.